Riparian Vegetation and Perception of Ecosystem Services in The Upper Gajahwong River, Yogyakarta, Indonesia - Sulistiyowati, Eka; Saputro, Dony Eko; Aisah, Siti (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Research on riparian vegetation and ecosystem services perception is essential to encourage community involvement in river area management. Therefore, this study aims to examine the composition of riparian vegetation along the upper Gajahwong River and assess local community perceptions of the ecosystem services provided by riparian biodiversity. Vegetation composition was studied through a floristic survey using plots placed along transects at three locations; Hargobinangun, Sardonoharjo, and Minomartani. Community perception was assessed through a survey of 60 randomly selected residents from the three villages studied. Data analysis involved calculating species richness, and species diversity, and analyzing community perceptions based on response percentages. The study identified more than 70 plant species at each site, with a very high diversity index (>4). Species with high Importance Value (IV) included Ficus racemosa (3.11), Dieffenbachia seguine (4.40), and Acalypha indica (3.59). Dominant plant families included Araceae, Fabaceae, and Moraceae, which provide essential provisioning and regulating ecosystem functions. Regarding community perception, the study found that residents recognized ecosystem functions, including provisioning services, regulating services, and socio-cultural services. Their understanding of ecosystem services was influenced by cultural values, particularly Javanese traditions emphasizing the importance of nature conservation.